Apakah Empati Mempengaruhi Kesadaran Pajak Generasi Z? - Sustiyo, Joko (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Research on the impact of empathy as a non-economic factor on tax awareness in Generation Z has not been widely studied in Indonesia. Most researchers still focus on economic factors. This study uses binary logistic regression analysis because the dependent variable is categorical. The significance of the regression equation parameters was tested by the Ratio Likelihood Test and the Wald Test. Then, the goodness of fit model was tested using the Hosmer-Lemeshow Test. The likelihood ratio test shows that there is at least one coefficient from the regression model that has an effect on the 5% significance level. Based on the Wald test, the independent variable empathic concern items have a significant effect on tax awareness with a 5% significance level. The Hosmer-Lemeshow test states that the binary logistic regression model in this study is feasible to use. Binary logistic regression analysis showed that only one predictor had a significant effect on the tax awareness variable, namely empathic concern items. The odds ratio value of 1.43 on the empathic concern items variable shows that the probability of a generation Z who has empathy will be 1.43 times more aware of taxes compared to respondents who do not have empathy